Implementasi Manajemen Sumber Daya Manusia Terhadap Kinerja Lembaga Pendidikan - Iswanto; Nur Fitri Hidayah; Siti Maryam; Muhammad Fadhil Ramadhan (STIT Syekh Muhammad Nafis Tabalong, 2024)
The influence of Human Resources Management (HR) on the Performance of Educational Institutions refers to how the practices and policies implemented in managing human resources in educational institutions influence the results or performance of the institution. The performance of educational institutions can be measured through various indicators such as teaching quality, student achievement, operational efficiency and staff satisfaction. By managing human resources effectively, educational institutions can improve overall performance, which will ultimately benefit students, staff and society at large. This research uses a qualitative approach, collecting data using observation, interviews and documentation. This research was conducted to find out how human resource management influences the performance of educational institutions, which refers more to the implementation implemented in an educational institution. Because educational institutions are more commonly known as schools, the researcher took the school as an object and conducted research at one of the schools in Sangatta, Kab. East Kutai MTs Hubbul Wathon. The researcher included several formulations of general problems that often occur in the implementation of human resources in an educational institution.